Effect of crystallization on tensile mechanical properties of PET foam: Experiment and model prediction. (October 2020) - Yao, Shun; Hu, Dongdong; Xi, Zhenhao; Liu, Tao; Xu, Zhimei; Zhao, Ling
Abstract: Currently Polyethylene terephthalate (PET) foam is the most promising structural core materials, and the tensile mechanical properties are one of its important application indicators. Herein, environmental-friendly supercritical CO2 (ScCO2 ) extrusion foaming was adopted to prepare PET foam. Aiming at investigating the influence of crystals on the mechanical properties, isothermal treatment in the post-process was used to improve the crystallization process of PET foams. Due to the crystal perfection proceeds via migration and rejection of the structural defects at the crystallites induced by slow crystallization, the crystallinity increased rapidly with the rise of isothermal temperature, especially above the glass transition temperature (Tg ). Qualitatively, it can be concluded that the crystalline phase contents have an intimate positive correlation with the tensile modulus, meanwhile, the shape ratio of the crystal have no significant effects on the tensile modulus. In addition, a coupling scheme of aggregate two-layered composite inclusion model and Simone-Gibson equation was first proposed to quantify the mathematical relationship between crystallization and tensile modulus of PET foam, which realized basic agreement. Highlights: Tensile properties of PET foams prepared by ScCO2 extrusion foaming were studied. Shape ratios of crystal had ignorable effect on the tensile modulus of PET foam. Isothermal treatment above Tg promoted mechanical performance of PET foam obviously. The composite inclusion model effectively predicted the tensile modulus of PET. A coupled scheme was proposed to evaluate the tensile modulus of PET foams.